Comparative characterization of fatty acids, reheating volatile compounds, and warmed-over flavor (WOF) of Chinese indigenous pork and hybrid pork. (1st February 2022) - Zhang, Kaihua; Li, Dan; Zang, Mingwu; Zhang, Zheqi; Li, Xiaoman; Wang, Shouwei; Zhang, Shunliang; Zhao, Bing
Abstract: Chinese indigenous pork is preferred by consumers because of its unique nutritional and flavor characteristics. The aim of this study was to investigate the fatty acid contents and reheating volatile compounds (i.e., warmed-over flavor (WOF)) of the biceps femoris muscle of four Chinese indigenous (i.e., Guangdong small-ear spotted, GSS; hill black, HB; Beijing black, BB; Qingyu, QY) and one hybrid (i.e., Duroc × Landrace × Yorkshire, DLY) pig breeds. Principal component analysis of 20 fatty acids and 30 reheating volatiles showed that five pig breeds could clearly be distinguished from each other. Among the pig breeds studied, GSS showed the lowest WOF contents and odor activity values (OAVs) (1251.87 μg/kg and 1111.64, respectively). Differences in WOF content and OAV among the four other breeds did not significantly differ ( P  > 0.05). Correlation analysis demonstrated that C16:1, C18:1, and C18:2 may be the key fatty acids of WOF formation. This study provides a new strategy for reducing the WOF of precooked meat products. Graphical abstract: Image 1 Highlights: 20 fatty acids and 30 reheating volatiles were identified in different pig breeds. Five kinds of porks were clearly discriminated by chemometrics analysis. C16:1, C18:1, and C18:2 exhibited strong positive correlation with WOF indicators. The WOF in GSS pork was significantly lowest based on content and OAV.